Keragaan dan Kemampuan Meratun Lima Genotipe Sorgum - Meliala, Merry Gloria; ,, Trikoesoemaningtyas; Sopandie, dan Didy (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Ratooning can be used as an alternative cultivation technique for production of sorghum. This study was aimed to evaluate the growth and production of ratoon following the main crop. The study was conducted during August 2013 until November 2014, at Cikabayan Experimental Station, Bogor Agricultural University. The research was arranged in a randomized complete block design with four replications. The results showed that genotypes was significantly affected the vegetative and reproductive characters, physiologycal characters of the main crop, ratooning ability, and vegetative characters of ratoon crop. Plant height, stem diameter, fresh and dry weight, harvest time, and harvest index of main crops had significant correlation with ratooning ability. Plant height, total chlorophyll, fresh and dry weight, panicle weight, grain weight per panicle, 1,000 grain weight, harvest index, and transpiration rate of main crops had significant correlation with ratoon growth. Based on path analysis, the main crop growth directly affected ratoon height, and vegetative characters of ratoon directly affected the yield. The ratoon yielded 48.9-65.7% of the main crop yield. Keywords: path analysis, ratooning ability, ratoon crops